2021
DOI: 10.1021/acs.analchem.1c01859
|View full text |Cite
|
Sign up to set email alerts
|

Functional Polysiloxane Enables Visualization of the Presence of Carbon Monoxide in Biological Systems and Films

Abstract: As an essential gasotransmitter, carbon monoxide (CO) had gradually become a research hotspot in that it possessed important physiological functions and unique pharmacological properties. However, to date, no report has focused on the topic of detecting CO both in vivo and using films. To open up a new field of CO probes, for the first time, we designed a probe (PMAH-CO) that showed a distinctive ratio emission characteristic and displayed the quantitative distribution of CO in HeLa cells and zebrafish with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Fluorescent biological imaging is considered one of the most commonly used detection methods due to its high sensitivity, selectivity, and versatility. Encouraged by the previously mentioned promising results of the sensing platform for solution-based CO detection, we evaluated the ability of the TPANN-Pd system for the “turn on” sensing of endogenous CO by cell-imaging in live Hela (human cervical cancer cells) utilizing SP8 confocal laser scanning microscopy. For potential bioimaging application in living cells, the cytotoxicity of the sensing platform was first explored with standard MTT assay with various concentrations from 1 to 20 μM of TPANN-Pd for 24 h (Figure S20).…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescent biological imaging is considered one of the most commonly used detection methods due to its high sensitivity, selectivity, and versatility. Encouraged by the previously mentioned promising results of the sensing platform for solution-based CO detection, we evaluated the ability of the TPANN-Pd system for the “turn on” sensing of endogenous CO by cell-imaging in live Hela (human cervical cancer cells) utilizing SP8 confocal laser scanning microscopy. For potential bioimaging application in living cells, the cytotoxicity of the sensing platform was first explored with standard MTT assay with various concentrations from 1 to 20 μM of TPANN-Pd for 24 h (Figure S20).…”
Section: Resultsmentioning
confidence: 99%
“…One can safely say that this publication by Michel, Lippert, and Chang started a wave of work on designing new small-molecule fluorescent probes for CO with various designs, including the use of Pd-catalyzed carbonylation and Pd-mediated deallylation for fluorophore activation in CO detection (Table S2). , We are very interested in such work because of our interest in carbonylation chemistry, CO detection, CO biology, , and CO donors as potential therapeutic agents. , Our interest in CO largely stems from the fact that CO is an endogenously produced molecule in mammals with demonstrated pharmacological effects. …”
Section: Introductionmentioning
confidence: 99%
“…Carbon monoxide (CO) is primarily considered to be explosive and have mammalian toxicity. , Nevertheless, recent studies revealed that CO can be generated endogenously by heme oxygenase (HO) in the heme of the human body and act as an important gasotransmitter in various physiological and pathological processes. The level of CO in cells and blood is always altered by pathological syndromes, such as lung disease, septicemia, diabetes, and cancer. , Thus, the real-time monitoring of CO in living cells and blood is an important alternative to diagnose a variety of diseases. Despite advances in CO detection, convenient and functional monitoring methods are still urgent to be developed. …”
Section: Introductionmentioning
confidence: 99%